2015
DOI: 10.1182/blood-2014-11-610329
|View full text |Cite
|
Sign up to set email alerts
|

The PI3K/mTOR inhibitor PF-04691502 induces apoptosis and inhibits microenvironmental signaling in CLL and the Eµ-TCL1 mouse model

Abstract: Key Points PF-04691502 induces potent apoptosis in CLL cells and suppresses prosurvival anti–immunoglobulin M signaling and CXCL12-induced migration. PF-04691502 displays powerful antitumor effects in vivo in the Eμ-TCL1 mouse model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…Attempts have been recently made to apply mTOR inhibitors in treatment of leukemia, including CLL [41, 42, 43]. Along the rationale presented above the patients with high level of RDW are expected to have an increased persistent level of IGF-1/mTOR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts have been recently made to apply mTOR inhibitors in treatment of leukemia, including CLL [41, 42, 43]. Along the rationale presented above the patients with high level of RDW are expected to have an increased persistent level of IGF-1/mTOR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] The PI3K-related protein kinase (PIKK) family includes mammalian target of rapamycin kinase (TORK), ataxia telangiectasia mutated (ATM), ataxia telangiectasia and Rad3 related (ATR), and DNA-dependent protein kinase (DNA-PK). TORK is the main downstream kinase of the PI3K/AKT pathway and exists in 2 protein complexes: mTORC1 and mTORC2.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, emerging evidence has revealed that the inhibition of MTOR signaling mediated the induction of apoptosis under various conditions; for instance, thymosin alpha 1 executed this effect in breast cancer [10]. It was reported that the inhibition of MTOR by pharmaceutical treatment, such as PF-04691502 [11], NVP-BEZ235 [12], and AZD8055 [13], can promote apoptosis, although these inhibitors affected MTOR activity through the indirect regulation of MTOR instead of the mediation of PI3K signaling. Indeed, some direct MTOR inhibitors have also been reported to induce apoptosis, for example, pp242 [14], temsirolimus [15], and everolimus [16].…”
Section: Introductionmentioning
confidence: 99%